Eficacia del sistema CRISPR-Cas9 en el abordaje de la farmacorresistencia bacteriana. Revisión Sistemática - Gómez Chamba, Dayanara Isabel (2024)
CRISPR-Cas9 is a genomic editing method that allows DNA modifications by recognizing and cutting specific DNA sequences. Antimicrobial resistance is a major public health threat and in Ecuador, there have been worrying cases of bacteria resistant to commonly used antibiotics. The CRISPR-Cas9 system could be able to reverse this resistance by eliminating or inactivating the genes responsible for it, restoring the bacteria susceptibility to antibiotics. Some studies have demonstrated its efficacy, showing promising results of its application in drug-resistant bacteria. This paper aims to review data on the application of CRISPR-Cas9 in drug-resistant bacteria, detailing the most susceptible bacteria, the modified genetic mechanisms, their clinical applicability, efficacy and implementation challenges. To this end, a systematic review developed including 17 quasi-experimental studies obtained from two databases: Pubmed and Scopus. They were all published in English between the years 2014-2024, and were evaluated through the JBI tool, evidencing a low risk of bias. The most susceptible bacteria were identified, with Escherichia coli being the main one (50%). The modified genetic mechanisms were detailed, from which the plasmid carrying mcr-1 (18.8%) stands out, and which is responsible for colistin resistance. In addition, the efficacy of CRISPR-Cas9 was evaluated by comparing the minimum inhibitory concentration before and after genomic editing, thus demonstrating that this method significantly in